BUSINESS PERFORMANCE ANALYSIS - MUSAEVA, Nasibakhon (Journal of Fundamental Studies, 2024)
A key instrument for assessing a company's financial performance and stability, financial accounting analysis forms the basis of strategic decision-making. The balance sheet, income statement, and cash flow statement are the three main financial statements that are thoroughly examined as part of this analytical process, which provides information about the entity's profitability, liquidity management, and overall financial health. By employing techniques such as financial ratio analysis, trend analysis, and industry benchmarking, analysts assess key financial aspects, including liquidity, solvency, operational efficiency, and profitability. A professional Business Performance Analysis is aimed to provide along with dashboard of past financial statements of one of the Pharmacy entities in Uzbekistan in 2022-2023, to visualizes the financial health and performance metrics of the company, particularly in managing costs and improving profitability in months where losses are indicated. Specifically, ratio calculation to identify the business performance and operational efficiency over the year, guiding decisions in management and investment targeted.